Annual Plan 1970-71 Jammu and Kashmir State - Planning Commission (Planning Commission, 1970)
Three years, at the national as well as state levels, for various reasons which need not be gone into here. Although its commencement year is 1969-70, the firm outlines of the national Fourth Plan did not emerge until about the end of that year. The first year of the IV Plan was therefore more or less a continuation of the ad-hoc Annual Plans which started at the end of the Third Plan, in 1966-67. It is only with effect from the year 1970-71 that the long term planning process has started once again. Hence the special importance of the Annual Plan for 1970-71, even though it happens to be the second year of the Fourth Plan.
Jammu and Kashmir State, Planning Department